The Planar Polarity Component VANGL2 Is a Key Regulator of Mechanosignaling - Cheong, Sek-Shir; Akram, Khondoker M.; Matellan, Carlos; Kim, Sally Yunsun; Gaboriau, David C. A.; Hind, Matthew; del Río Hernández, Armando E.; Griffiths, Mark; Dean, Charlotte H. (Frontiers in Cell and Developmental Biology, 2020)
VANGL2 is a component of the planar cell polarity (PCP) pathway, which regulates tissue polarity and patterning. The Vangl2Lp mutation causes lung branching defects due to dysfunctional actomyosin-driven morphogenesis. Since the actomyosin network regulates cell mechanics, we speculated that mechanosignaling could be impaired when VANGL2 is disrupted. Here, we used live-imaging of precision-cut lung slices (PCLS) from Vangl2Lp/+ mice to determine that alveologenesis is attenuated as a result of impaired epithelial cell migration. Vangl2Lp/+ tracheal (TECs) and alveolar epithelial cells exhibited highly disrupted actomyosin networks and focal adhesions. Functional assessment of cellular forces confirmed impaired traction force generation in Vangl2Lp/+ TECs. YAP signaling in Vangl2Lp airway epithelium was reduced, consistent with a role for VANGL2 in mechanotransduction. Furthermore, activation of RhoA signaling restored actomyosin organization in Vangl2Lp/+, confirming RhoA as an effector of VANGL2. This study identifies a pivotal role for VANGL2 in mechanosignaling, which underlies the key role of the PCP pathway in tissue morphogenesis.